2021
DOI: 10.1080/21691401.2021.1925678
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted green synthesis of silver nanoparticles for optical, catalytic, biological and electrochemical applications

Abstract: Plant-derived nanoparticles have multi-functionalities owing to their ecological origin and biocompatible nature. A novel and stable silver nanoparticle (AgNP) was reported here using Cyanthillium cinereum (C. cinereum) as a reducing as well as capping agent by rapid microwave-assisted green method. The synthesized nanoparticles revealed their crystalline and spherical nature with an average size of 19.25 ± 0.44 nm in HR-TEM analysis. The excitation of electrons from occupied d-bands to states above the Fermi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…These results agree well with the previous reports on the antioxidant property of the biofabricated Ag-NPs using extracts, including plant extracts [ 52 ], bacteria [ 47 ], cyanobacteria [ 53 ], and microalgae [ 54 ]. The antioxidant characteristics of nanoparticles are mostly determined by the methods used in nanoparticle preparation and the ability of the living organism to adapt to harsh environmental conditions, such as cyanobacteria's phototrophic existence and constant exposure to high oxygen and radical stressors.…”
Section: Resultssupporting
confidence: 93%
“…These results agree well with the previous reports on the antioxidant property of the biofabricated Ag-NPs using extracts, including plant extracts [ 52 ], bacteria [ 47 ], cyanobacteria [ 53 ], and microalgae [ 54 ]. The antioxidant characteristics of nanoparticles are mostly determined by the methods used in nanoparticle preparation and the ability of the living organism to adapt to harsh environmental conditions, such as cyanobacteria's phototrophic existence and constant exposure to high oxygen and radical stressors.…”
Section: Resultssupporting
confidence: 93%
“…The resultant AgNPs were found to demonstrate antibacterial activity toward bacterial species such as Klebsiella pneumoniae and Staphylococcus aureus . In addition, it was suggested that the resultant nanoparticles can be employed as promising Candida tes in applications as biosensors and nonenzymatic electrochemical sensors [ 180 ].…”
Section: Strategies For Green Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…In FTIR spectrum, the strong absorption peak at 1084.03 cm -1 can be attributed to -C-O stretching vibrations in the carboxyl group and denoted stretching vibrational bands responsible for compounds like flavonoids (Siddiqui et al, 2000) be held responsible for efficient capping and stabilisation of formed AgNPs. The sharp band at 823.63 cm -1 was due to an aromatic ring (Anjana et al, 2021).The C=O stretch at 1660.77 cm -1 represented the presence of amide. The strong,broader, and highest absorption peaks referring to N=O bend at 1383.01 cm -1 was attributed to the nitro compounds.The stretching vibrations at 2883.68 cm -1 indicated the presence of alkane groups.The short C=O stretching vibration at 1784.21 cm -1 corresponded to either aldehydes or ketones or ester group.…”
Section: Discussionmentioning
confidence: 98%